Sociologia esistenziale: per un materialismo dematerializzato - Tognonato, Claudio (SocietàMutamentoPolitica, 2019)
This paper presents an attempt to reconcile the opposing viewpoints of philosophy and sociology through existential sociology. Its starting point is the notion of freedom, which is central to existential philosophy. If a human being is free, even ‘condemned to be free’, why in our experience do we mostly perceive that we are not? Why do we have the opposite feeling? To answer this question the article focuses on the notion of practico-inert, a term coined by Jean-Paul Sartre in the Critique of Dialectical Reason (1960). Practical activities and material structures, learnt or inherited from previous generations, have the effect of limiting or nullifying true freedom of action. The practico-inert expresses the exigency of matter or of mute, inanimate objects as a sort of inert, imposed finality. Material exigencies become a crucial category of the Critique for characterizing the way we experience and respond to the force of materiality, which every time becomes a dematerialized material.